2011
DOI: 10.1203/pdr.0b013e3182084e54
|View full text |Cite
|
Sign up to set email alerts
|

Development of Corpus Callosum in Preterm Infants Is Affected by the Prematurity: In Vivo Assessment of Diffusion Tensor Imaging at Term-Equivalent Age

Abstract: Callosal injury in preterm infants is a key factor affecting neurodevelopmental outcome. We investigated the characteristics of corpus callosum (CC) in preterm infants without apparent white matter lesions. We studied 58 preterm infants divided into three groups of 23-25, 26 -29, and 30 -33 wk GA. Diffusion tensor imaging (DTI) was obtained at term-equivalent age. The CC was parcellated into the genu, body, isthmus, and splenium. We measured fractional anisotropy (FA) and apparent diffusion coefficient (ADC) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 37 publications
5
39
0
Order By: Relevance
“…Multiple regression analysis showed that the FA in the CC increased linearly with the GA at birth. A similar finding was reported by Hasegawa et al [23]; however, de Bruïne et al [24] found no significant maturation trends between the CC and GA at birth. At present, we cannot clearly explain why only the FA of the CC was dependent on GA but not on PMA.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Multiple regression analysis showed that the FA in the CC increased linearly with the GA at birth. A similar finding was reported by Hasegawa et al [23]; however, de Bruïne et al [24] found no significant maturation trends between the CC and GA at birth. At present, we cannot clearly explain why only the FA of the CC was dependent on GA but not on PMA.…”
Section: Discussionsupporting
confidence: 88%
“…At present, we cannot clearly explain why only the FA of the CC was dependent on GA but not on PMA. Previous studies reported that younger GA is related to smaller callosal size and altered callosal microstructure in preterm infants and that these are linked to poor neurological outcomes [7,11,23,25]. Impairment of callosal growth is suggested as a potential indicator of cerebral axonal disturbance [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 However, diffusion tensor imaging studies that have focused on the callosal splenium have shown disparate results; 1 study of preterm infants at term-equivalent age found significant differences compared with term infants, while another found no definite relationship between gestational age and changes in various DTI parameters. 28,29 Theoretically, another possibility may relate to a phenomenon called the "visual experience" hypothesis, which essentially states that because preterm infants are "out" of the mother longer by the time of term-equivalent imaging (relative to full-term neonates), healthy premature infants would have experienced a greater degree of visual stimulation and thus would have accelerated maturation of visual pathways by the same postnatal gestational age. 30 Most interesting, studies using visualevoked potentials and contrast sensitivities have suggested accelerated maturation of the visual cortices in preterm relative to term infants, which might have manifested in the current study as earlier visualization of callosal splenium maturation in the preterm infants imaged at term-equivalent age.…”
Section: Percentages and Numbers Of Term Infants With Myelinationmentioning
confidence: 99%
“…DTI is an MR imaging technique used to characterize the microstructure of large WM tracts in physiologic and pathologic conditions and provides complex measures that reflect various microstructural properties of the WM, including axon diameter, myelination, and fiber attenuation. 17 Microstructural changes in the CC have been described with DTI studies in premature infants, 18 extremely preterm infants, 19 very-low-birth-weight adolescents, 20 and preterm born young adults. 21 The overall aims of this study were to prospectively investigate WM microstructural development in the interhemispheric brain connectivity in neonates with d-TGA before and after CPB.…”
mentioning
confidence: 99%